Pesan Dakwah dalam Buku Humor Karya Mustofa Bisri - Lukman Ramdani; Sitty Sumijati; Heny Gustini Nuraeni (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2017)
This study aims to find out the message categories of dakwah, message organization, and appeal messages contained in the book “Canda Nabi dan Sufi Hingga Kelucuan Kita” by Mustofa Bisri. The method used in this research is content analysis with descriptive approach. This analysis is done by identifying categories, organization, and appeal messages on the book and the message category of dakwah, organization of messages, and appeal messages on each theme of the story. The results of the research found that the categories of messages contained in the book “Canda Nabi dan Sufi Hingga Kelucuan Kita” is message Akidah, Shariah, and Akhlak. The more prominent Message of Aqeedah in this book is the message of Aqeedah with a sub category of faith in God. The message organization in this book is a deductive, inductive, chronological, logical, topical, and spatial pattern. While the more dominant message organization is chronological pattern. The message implied in this book is a rational, emotional, and motivational appeal. A more dominant appeal is a rational appeal and an emotional appeal. Penelitian ini bertujuan untuk mengetahui kategori pesan dakwah, organisasi pesan dakwah, dan imbauan pesan dakwah yang terkandung dalam buku “Dari Canda Nabi dan Sufi hingga Kelucuan Kita” Karya Mustofa Bisri. Metode yang digunakan pada penelitian ini adalah analisis isi dengan pendekatan deskriptif. Analisis ini dilakukan dengan mengidentifikasi kategori, organisasi, dan imbauan pesan pada buku dan pada tiap-tiap tema cerita. Hasil penelitian yang ditemukan menunjukan bahwa kategori pesan yang terkandung dalam buku “Dari Canda Nabi dan Sufi Hingga Kelucuan Kita” ialah pesan akidah, syariah, dan akhlak. Pesan akidah yang lebih menonjol dalam buku ini adalah pesan akidah dengan sub kategori iman kepada Allah. Organisasi pesan dalam buku ini adalah pola deduktif, induktif, kronologis, logis, topikal, dan spasial. Sedangkan organisasi pesan yang lebih dominan adalah pola kronologis. Imbauan pesan yang ada dalam buku ini adalah imbauan rasional, emosional, dan motivasional sedangkan imbauan yang lebih dominan adalah imbauan rasional dan imbauan emosional.